2020
DOI: 10.1371/journal.ppat.1008372
|View full text |Cite
|
Sign up to set email alerts
|

Commensal Neisseria cinerea impairs Neisseria meningitidis microcolony development and reduces pathogen colonisation of epithelial cells

Abstract: It is increasingly being recognised that the interplay between commensal and pathogenic bacteria can dictate the outcome of infection. Consequently, there is a need to understand how commensals interact with their human host and influence pathogen behaviour at epithelial surfaces. Neisseria meningitidis, a leading cause of sepsis and meningitis, exclusively colonises the human nasopharynx and shares this niche with several other Neisseria species, including the commensal Neisseria cinerea. Here, we demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 54 publications
(95 reference statements)
0
21
0
Order By: Relevance
“…Little is known about production of secondary metabolites by Neisseria , however, some nonpathogenic species have been shown to inhibit pathogens. N. lactamica ( Deasy et al, 2015 ) and N. cinerea ( Custodio et al, 2020 ) inhibit the colonization of N. meningitidis in human infection and epithelial cell culture models, respectively, and DNA released by N. elongata and multiple other nonpathogenic Neisseria species kills N. gonorrhoeae ( Kim et al, 2019 ). In the project described here, we initiated a search for neisserial antimicrobial secondary metabolites by analyzing a panel of 36 nonpathogenic Neisseria strains for activity against other Neisseria , including N. gonorrhoeae.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about production of secondary metabolites by Neisseria , however, some nonpathogenic species have been shown to inhibit pathogens. N. lactamica ( Deasy et al, 2015 ) and N. cinerea ( Custodio et al, 2020 ) inhibit the colonization of N. meningitidis in human infection and epithelial cell culture models, respectively, and DNA released by N. elongata and multiple other nonpathogenic Neisseria species kills N. gonorrhoeae ( Kim et al, 2019 ). In the project described here, we initiated a search for neisserial antimicrobial secondary metabolites by analyzing a panel of 36 nonpathogenic Neisseria strains for activity against other Neisseria , including N. gonorrhoeae.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, one way for susceptible bacteria to evade T6SS killing is to avoid direct contact with attacking cells (Borenstein et al, 2015; Smith et al, 2020). In Neisseria , the Tfp is a key mediator of interbacterial and interspecies interactions (Custodio et al, 2020; Higashi et al, 2011b) and pilus-mediated interactions influence the spatial structure of a growing community (Oldewurtel et al, 2015; Zöllner et al, 2017). In N. gonorrhoeae, non-piliated bacteria segregate to the expanding front of the colony and Tfp-mediated spatial reorganisation can allow bacteria to avoid external stresses or strains competing for resources (Oldewurtel et al, 2015; Zöllner et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The human nasopharynx hosts a polymicrobial community (Kumpitsch et al, 2019; Marchesi et al, 2017; Ramos-Sevillano et al, 2019), which can include the obligate human pathobiont Neisseria meningitidis , as well as related but generally non-pathogenic, commensal Neisseria species (Diallo et al, 2016; Dorey et al, 2019; Gold et al, 1978; Knapp and Hook, 1988; Sheikhi et al, 2015). In vivo studies have demonstrated an inverse relationship between carriage of commensal Neisseria lactamica and N. meningitidis (Deasy et al, 2015), while in vitro studies have revealed that some commensal Neisseria demonstrate potentially antagonistic effects against their pathogenic relatives (Custodio et al, 2020; Kim et al, 2019). Commensal and pathogenic Neisseria species have also been shown to interact closely in mixed populations (Custodio et al, 2020; Higashi et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations